Presence and distribution of the endosymbiont Wolbachia among Solenopsis spp. (Hymenoptera: Formicidae) from Brazil and its evolutionary history - Martins, Cíntia [UNESP]; Souza, Rodrigo Fernando [UNESP]; Bueno, Odair Correa [UNESP] (Elsevier, 2012)
Wolbachia are intracellular bacteria that commonly infect arthropods. Its prevalence among ants of the genus Solenopsis is high. In the present study, the presence and distribution of these endosymbionts was examined among populations of Solenopsis spp. from Brazil. A phylogenetic analysis based on the wsp gene was conducted to infer the evolutionary history of Wolbachia infections within the populations surveyed. A high frequency of Wolbachia bacteria was observed among the genus Solenopsis, 51% of the colonies examined were infected. Incidence was higher in populations from southern Brazil. However, little genetic variability was found among different Wolbachia strains within supergroups A and B. Our findings also suggest that horizontal transmission events can occur through the social parasite S. daguerrei. © 2012 Elsevier Inc..
Keywords: Phylogenetic analysis; Solenopsis invicta; Solenopsis saevissima; Wolbachia; Wsp; outer membrane protein; Wsp protein, Wolbachia; amino acid sequence; animal; ant; Brazil; classification; disease transmission; evolution; gene; genetics; Gram negative infection; microbiology; molecular genetics; reverse transcription polymerase chain reaction; Amino Acid Sequence; Animals; Ants; Bacterial Outer Membrane Proteins; Biological Evolution; Disease Transmission, Infectious; Genes, Insect; Gram-Negative Bacterial Infections; Molecular Sequence Data; Reverse Transcriptase Polymerase Chain Reaction; Arthropoda; Bacteria (microorganisms); Formicidae; Hymenoptera; Solenopsis; Solenopsis daguerrei